Psychometric Properties and Network Analysis of the Arabic Version of Reinforcement Sensitivity Theory of Personality Scale-Short Version in Patients with Anxiety Disorders - Rasha Mohamed Abdelrahman (22282804) (2025)
This study aimed to examine the psychometric properties of the Arabic version of a short version of the Reinforcement Sensitivity Theory of Personality Questionnaire (RST-PQ-S) among a sample of 700 patients with anxiety disorders (53.1% were female). Participants completed the RST-PQ-S, NEO-FFI, Positive Mental Health (PMH), and Kessler Psychological Distress scale. Both Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were employed to test the construct validity of the scale. This study also utilized a network perspective, incorporating Exploratory Graph Analysis (EGA) and centrality measures. As a result of the EFA and CFA, it was determined that the scale consists of 22 items and six subdimensions. These subdimensions were named as follows: “Flight Fight-Freeze System”, “Behavioral Inhibition System”, “Reward Interest”, “Reward Reactivity”, “Goal-Drive Persistence”, and “Impulsivity”. Additionally, the network analysis’s findings confirmed the six-factor structure derived from the construct validity assessment. The results of this study demonstrated that the Arabic version of the personality scale is a valid and reliable tool for assessing personality in Arabic-speaking individuals with anxiety disorders. It has the potential to serve as an important diagnostic instrument in clinical and research settings. These findings may assist psychologists and clinicians in Arabic-speaking countries to better understand how the personality traits and anxiety disorders are related. Other Information Published in: Psychiatric Quarterly License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11126-024-10109-3